Registers Analysis on Tiktok Women Fashion Shop Live - Khansa, Syifa Nadiah; Sijabat, Carissa Margaret; Marsha, Siti Azzahra; Sitompul, Riyadhil; Rangkuti, Rahmadsyah (Universitas Pahlawan Tuanku Tambusai, 2024)
This study investigates the language registers used by women’s clothes sellers during TikTok Live sessions, with an emphasis on the specific usage of words and phrases to promote communication in a fast-paced sales setting. A qualitative investigation of live-stream interactions finds that nouns (41.86%) are utilized to offer precise product descriptions, followed by verbs, adjectives, abbreviations, and compound words. Nouns are very useful for expressing product information like stock availability, sizes, and materials. The study differentiates between lexical and contextual meanings, with lexical meanings (60.47%) taking precedence, providing precise definitions that improve intelligibility for potential purchasers. Contextual meanings, while less common, are essential for sustaining dynamic connections with the audience. Contextual meanings, while less common, are essential for sustaining dynamic connections with the audience. The findings emphasize how vendors use clear product information and casual language to increase engagement and purchases. This study suggests that the language methods used on TikTok Lives are highly flexible, combining product clarity with audience engagement in order to maximize the sales process.